Conservation of shibire and RpII215 temperature-sensitive lethal mutations between Drosophila and Bactrocera tryoni - Nguyen, Thu N. M.; Choo, Amanda; Baxter, Simon W. (Frontiers in Insect Science, 2024)
The sterile insect technique can suppress and eliminate population outbreaks of the Australian horticultural pest, Bactrocera tryoni, the Queensland fruit fly. Sterile males mate with wild females that produce inviable embryos, causing population suppression or elimination. Current sterile insect releases are mixed sex, as the efficient removal of unrequired factory-reared females is not yet possible. In this paper, we assessed the known Drosophila melanogaster temperature-sensitive embryonic lethal alleles shibire (G268D, shits1) and RNA polymerase II 215 (R977C, RpII215ts) for potential use in developing B. tryoni genetic sexing strains (GSS) for the conditional removal of females. Complementation tests in D. melanogaster wild-type or temperature-sensitive genetic backgrounds were performed using the GAL4–UAS transgene expression system. A B. tryoni wild-type shibire isoform partially rescued Drosophila temperature lethality at 29°C by improving survivorship to pupation, while expressing B. tryoni shits1 failed to rescue the lethality, supporting a temperature-sensitive phenotype. Expression of the B. tryoni RpII215 wild-type protein rescued the lethality of D. melanogaster RpII215ts flies at 29°C. Overexpressing the B. tryoni RpII215ts allele in the D. melanogaster wild-type background unexpectedly produced a dominant lethal phenotype at 29°C. The B. tryoni shibire and RpII215 wild-type alleles were able to compensate, to varying degrees, for the function of the D. melanogaster temperature-sensitive proteins, supporting functional conservation across species. Shibire and RpII215 hold potential for developing insect strains that can selectively kill using elevated temperatures; however, alleles with milder effects than shits1 will need to be considered.